2016
DOI: 10.1016/j.jphotobiol.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical characterization of anticancer drug valrubicin in rHDL nanoparticles and its use as an imaging agent

Abstract: Nanoparticles are target-specific drug delivery agents that are increasingly used in cancer therapy to enhance bioavailability and to reduce off target toxicity of anti-cancer agents. Valrubicin is an anti-cancer drug, currently approved only for vesicular bladder cancer treatment because of its poor water solubility. On the other hand, valrubicin carrying reconstituted high density lipoprotein (rHDL) nanoparticles appear ideally suited for extended applications, including systemic cancer chemotherapy. We dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Synthetic HDL nanoparticles could act synergistically and lessen the amount of mitotane/etoposide/cisplatin needed for anticancer efficacy in adrenocortical carcinoma [154]. The binding of anticancer drug valrubicin with rHDL increases the water solubility of valrubicin, which appears ideally suited for extended applications, including systemic cancer chemotherapy [155]. Artificial HDL nanoparticles using a gold nanoparticle induce B lymphoma cell apoptosis through SR-BI-mediated cholesterol starvation and selectively inhibit B-cell lymphoma growth in mice [156].…”
Section: Hdl: Nature's Nanoparticlesmentioning
confidence: 99%
“…Synthetic HDL nanoparticles could act synergistically and lessen the amount of mitotane/etoposide/cisplatin needed for anticancer efficacy in adrenocortical carcinoma [154]. The binding of anticancer drug valrubicin with rHDL increases the water solubility of valrubicin, which appears ideally suited for extended applications, including systemic cancer chemotherapy [155]. Artificial HDL nanoparticles using a gold nanoparticle induce B lymphoma cell apoptosis through SR-BI-mediated cholesterol starvation and selectively inhibit B-cell lymphoma growth in mice [156].…”
Section: Hdl: Nature's Nanoparticlesmentioning
confidence: 99%
“…Fluorescence based studies reported by Shah et al (2016) showed that the drug valrubicin has differential optical properties when encapsulated in rHDL. Moreover, valrubicin has low quantum yield in aqueous environment and it increases several fold when incorporated into rHDL nanoparticles.…”
Section: Sr-b1 As a Conduit For The Delivery Of Imaging Agentsmentioning
confidence: 99%
“…Development of rHDL nanoparticles that mimic pre-β HDLs, could promote cholesterol efflux from lipid-enriched macrophages, thereby reducing atherosclerosis. Many different rHDL nanoparticles (apoAI-bound phospholipid disks or delipidated HDL particles, mutant apoAI proteins, and apoAI mimetic peptides) have been constructed and investigated in animal studies and human clinical trials [51].…”
Section: Reconstituted High-density Lipoprotein (Rhdl) Nanoparticlesmentioning
confidence: 99%